The Impact of Hospital Advertising on Patient Choices: Views from Health Service Users - Şeyma Boz; Ümit Çıraklı; Seda Kumru (Sakarya Üniversitesi İşletme Enstitüsü Dergisi)
This study aims to determine the attitudes of healthcare users toward the advertising activities conducted by private hospitals, as well as the role of these advertisements in hospital selection. Data were gathered through a questionnaire administered to individuals who sought services at a private hospital in Istanbul. A total of 360 responses were analyzed using the SPSS (Statistical Package for Social Sciences) 21.0 program. The findings indicate that over 70% of participants believe that hospital advertisements provide useful information, offering insights into the qualifications of the hospital and the services it provides, thereby helping patients make more informed choices. However, the two main negative aspects of advertisements identified by participants are that they are often misleading and not sufficiently reliable. Overall, the study suggests that people generally hold positive opinions about private hospital advertisements.